Symptomatic Protective Action of Glycyrrhizin (Licorice) in COVID-19 Infection? - Murck, Harald (Frontiers in Immunology, 2020)
The role of the ACE2 enzyme in the COVID-19 infection is twofold, with opposing implications for the disease development. 1. The membrane bound angiotensin converting enzyme 2 (ACE2) serves as the entry point of COVID-19 2. Conversely, it supports an anti-inflammatory pathway. This led to the controversy of the impact of medications, which influence its expression. ACE2 is part of the wider renin-angiotensin-aldosterone system (RAAS) and is upregulated via compounds, which inhibits the classical ACE, thereby plasma aldosterone and aldosterone receptor (MR) activation. MR activation may therefore protect organs from binding the COVID-19 by reducing ACE2 expression. Glycyrrhizin (GL) is a frequent component in traditional Chinese medicines, which have been used to control COVID-19 infections. Its systemically active metabolite glycyrrhetinic acid (GA) inhibits 11beta hydroxysteroid dehydrogenase(11betaHSD2) and activates MR in organs, which express this enzyme, including the lungs. Does this affect the protective effect of ACE2?. Importantly, GL has anti-inflammatory properties by itself via toll like receptor 4 (TLR4) antagonism and therefore compensates for the reduced protection of the downregulated ACE2. Finally, a direct effect of GL or GA to reduce virus transmission exists, which may involve reduced expression of type 2 transmembrane serine protease (TMPRSS2), which is required for virus uptake. Glycyrrhizin may reduce the severity of an infection with COVID-19 at the two stages of the COVID-19 induced disease process, 1. To block the number of entry points and 2. provide an ACE2 independent anti-inflammatory mechanism.